George Amabile on War, Trauma, the Creative Process, and His Latest Collection Martial Music - Cusmano, Liana (Italian Canadiana)

(untitled) (Iter Press, 2020)
Liana Cusmano’s interview with poet George Amabile focuses on his prize-winning 2018 collection Martial Music and the art of writing in general. He offers insights on the poetic process, how to research and produce a collection of poems. Amabile’s poetry is inspired by what he has experienced or witnessed. He talks about dealing with war and trauma. He shares his frustration with daily life getting in the way of the creative process. “Life is the subject and the inspirational/ motivational source of our work, but it also sucks up our time and frustrates our ability to give our unstinted attention to our creative efforts,” says George Amabile.